1986
DOI: 10.1080/03079458608436284
|View full text |Cite
|
Sign up to set email alerts
|

Comparison ofin vivoandin vitromethods for pathogenicity evaluation formycoplasma gallisepticumin respiratory infection

Abstract: This study was designated to examine the pathogenicity of several strains of Mycoplasma gallisepticum (R, F, S-6, 227 and A5969) and laboratory derived substrains. Preliminary results indicated that the nine M. gallisepticum strains differed markedly in their pathogenicity for chickens. A comparison was made between various in vivo and in vitro methods for quantitative evaluation of pathogenicity. Reproducibility, convenience, and relevance to clinical observations were considered. Two in vivo tests were emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 19 publications
6
50
0
1
Order By: Relevance
“…The 6/85-and ts-11-based vaccines are reported to be safer than the F strain vaccine but do not afford the same level of protection [22,23,[28][29][30]. R high was previously reported to be avirulent for chickens [10] but the genetic changes associated with attenuation were only recently determined on a biochemical and molecular basis by Papazisi et al [11]. They reported that three proteins are absent in M. gallisepticum R high including the primary cytadhesin molecule, GapA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6/85-and ts-11-based vaccines are reported to be safer than the F strain vaccine but do not afford the same level of protection [22,23,[28][29][30]. R high was previously reported to be avirulent for chickens [10] but the genetic changes associated with attenuation were only recently determined on a biochemical and molecular basis by Papazisi et al [11]. They reported that three proteins are absent in M. gallisepticum R high including the primary cytadhesin molecule, GapA.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive in vitro passage of this organism gave rise to a highly attenuated strain "R high " that produces little if any pathology in chickens, even when used at doses 10,000-fold higher than a pathogenic dose of R low [10]. Previous studies have demonstrated that mutations in M. gallisepticum R high resulted in the loss of expression of three proteins, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Another method that has been used to deliver MG to the respiratory system is through the use of aerosols (Rodriguez & Kleven, 1980;Levisohn et al, 1986). Intratracheal instillation was chosen as a similar means of infection without the need for specialized aerosol generation equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Many infection model systems have been used, including those looking at disease status such as air sac and tracheal pathology (Rodriguez & Kleven, 1980;Levisohn et al, 1986;Nunoya et al, 1987), and those investigating production parameters such as egg production, egg quality, and weight gain (Branton & Deaton, 1985). Production parameter experiments generally require a significantly longer experiment, but the results are directly applicable to real-world conditions.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,22 A variety of procedures have been used to differentiate this heterologous population. Cultural, immunologic, and bird inoculation characteristics of isolates have limited differentiation ability other than to classify isolates as variant MG. 1,10,14,20,21 Cellular protein profiles can differentiate strains; however, banding patterns are complex and influenced by culture and electrophoretic conditions. 7,17,19 Several procedures used to examine genomic characteristics of MG have demonstrated a wide degree of variability among strains.…”
mentioning
confidence: 99%